Thrombosis of portal, superior mesenteric, and splenic veins: a case report - Soghomonyan, N.; Khachatryan, H.; Soghomonyan, G.; Fleming, Q. (Frontiers in Pharmacology, 2023)
Patients with venous thrombosis of splanchnic circulation represent a group of high risk with significant morbidity and mortality, if treatment is delayed. We present a patient with thrombosis of portal vein and its tributaries combined with deep venous thrombosis (DVT) of the lower extremities who was successfully treated with conservative management. This patient case highlights the importance of early empiric anti-inflammatory therapy along with systemic anticoagulation to reduce the intestinal inflammation and enteritis and break the vicious circuit resulting in secondary progressive thrombosis of the splanchnic veins, fluid shifts, and functional ileus. Case presentation: A previously healthy 61-years-old female patient with no significant medical history was admitted with progressive upper abdominal pain, nausea and vomiting, low-grade fever, mild signs of ileus, and malaise. Imaging studies revealed portal venous dilation reaching ∼20 mm with near-total obliteration of the lumen by a thrombus. In addition, thrombosis of superior mesenteric and splenic veins with thrombophlebitis was found. Imaging studies also confirmed the presence of DVT of lower extremities including thrombus propagation into the iliac veins. An immediate therapy was started with parenteral antibiotics, anti-inflammatory medications, systemic anticoagulants, and intravenous fluid infusions to restore the circulating volume deficit and treat electrolyte disbalance. With such therapy, the patient’s symptoms resolved within a month, and she was discharged from the hospital with full recovery. Heparin infusion was started to reach systemic anticoagulation. With resolution of symptoms, anticoagulation was continued with warfarin. We used non-steroidal anti-inflammatory drugs (NSAIDs) as a component in management of intestinal and systemic inflammation and multifocal thrombosis when the antiphospholipid syndrome was also on the list of differential diagnoses. Conclusion: We present a previously asymptomatic patient with progressive portal venous thrombosis and ascending DVT. Early establishment of diagnosis and initiation of therapy with systemic anticoagulants, anti-inflammatory and antibacterial drugs helped to stop thrombus progression, prevent irreversible intestinal ischemia, and allow for re-canalization of the occluded veins. This case highlights the importance of early interventions to improve the treatment outcome.